Over-Expression of GUSB Leads to Primary Resistance of Anti-PD1 Therapy in Hepatocellular Carcinoma - Kong, Xiangyi; Zheng, Zhiying; Song, Guoxin; Zhang, Zihao; Liu, Hanyuan; Kang, Junwei; Sun, Guoqiang; Sun, Guangshun; Huang, Tian; Li, Xiao; Rong, Dawei; Wang, Ke; et al. (Frontiers in Immunology, 2022)
Treatment with immunotherapy, particularly immune checkpoint blockade, can lead to benefit in the clinical setting. However, many preclinical and clinical studies suggest that resistance to anti-PD1 treatment frequently occurs, resulting in tumor relapse and treatment failure in cancer including hepatocellular carcinoma (HCC) patients. In this study ,10 HCC patients were treated with anti-PD1, and the biopsy samples before treatment were used for 289 nanostring panel RNA sequencing to compare responding and non-responding tumors to find possible pretreatment biomarkers or targets of the anti-PD1 therapy response. Fortunately, the expression of β-Glucuronidase (GUSB) in the non-responding tumors group was found significantly higher than that in the responding group. Results of cell counting kit 8(CCK8), clone forming, 5-ethynyl-2’-deoxyuridine (EdU), transwell ,wound healing assay ,flow cytometry showed that GUSB facilitated the proliferation, invasion and migration of human HCC cells and down-regulated PD-L1 expression. In addition, amoxapine acting as GUSB inhibitors decreased the progression of human HCC cells and worked as an effective means to treat HCC and improved the sensitivity of anti-PD1 therapy. In summary, the present study reveals that increased GUSB inhibits the expression of PD-L1, leading to primary resistance to anti-PD1 therapy in HCC, and the use of amoxapine enhances the sensitivity of anti-PD1 therapy via inhibiting GUSB in HCC,which provides a new strategy and method for improving the therapeutic effect of anti-PD-1 therapy, and brings new hope for the treatment of HCC.